Utilising pulse wave velocity in assessing arterial stiffness in patients with mild-to-moderate renal impairment / Ahmad Bakhtiar Md Radzi - Md Radzi, Ahmad Bakhtiar (2016)
Introduction: Chronic kidney disease (CKD) is associated with increased arterial stiffness. Identification of arterial stiffness in early chronic kidney disease patients is important as they are at risk of developing cardiovascular disease. This will allow risk stratification and allocation of resource in managing this high risk group. Existing literature revealed variable findings on arterial stiffnes in early CKD patients. Objective: We aim to compare arterial stiffness using pulse wave velocity (PWV) among patients with chronic kidney disease stage 2-4 and those with normal renal function. Methodology: This is a case-control study of CKD and normal renal function patients. Patients with confirmed chronic kidney disease stage 2 to 4 were recruited from various clinics in the Faculty of Medicine, Universiti Teknologi MARA, Sungai Buloh Campus, Malaysia from 1st August 2015 until 31th January 2016. Sociodemographic and anthropometric indices were recorded at recruitment. Each patient underwent a carotid-femoral (aortic) PWV measurement to determine the arterial stiffness. PWV is determined automatically with a dedicated one-probe device (SphygmoCore XCEL) in which the recorded pulse wave forms were obtained transcutaneously over the common carotid artery.